Ambition Of Greg Heffley Reflected In Jeff Kinney Diary Of Wimpy Kid 2 Novel (2008): A Psychoanalytic Approach - Widyarini, Risa, Drs. Abdillah Nugroho, M. Hum, Titis Setyabudi, S.S. M. Hum (2014)
The problem of this study is the ambition to live is very important to achieve success in life Greg Heffley‟s Diary of wimpy kid 2 novels. The purpose of this study was to analyze the novel based on the structural elements and analyze the novel based on psychoanalytic approach. The type of this research is qualitative research. This type of research data is text and images taken from two data sources: primary and secondary. The primary data source is the Diary of a wimpy kid 2 novels by author Jeff Kinney in 2008. While secondary data sources are other materials taken from books, author biographies, essays, comments, criticisms and internet-related research. Both the data collected by conducting library research and analyzed with descriptive analysis. Based on the analysis, the author describes some conclusions. First, based on the structural analysis of each element, it shows that the character and characterization, setting, plot, point of view, theme, mise-en scene, cinematography, sound, casting and editing support each other to produce a good quality novel. Secondly, based on psychoanalytic analysis, the study showed that the problems faced by the main character is a psychological condition yourself to determine the right way to life. This novel also shows the determination process involving large will produce amazing results.